Evaluation of Role of Lung Ultrasound in Childhood Pneumonia: An Institutional Based Study - S R Chauhan; Ghanshyam G. Patel (Asian Journal of Medical Radiological Research, 2014)
Background: Pneumonia is more prevalent in early childhood than in any other age group. Numerous studies conducted over the past decade have focused on the challenges associated with the diagnosis and management of pediatric pneumonia. Hence; the present study was conducted to evaluate the role of lung ultrasound in childhood pneumonia. Materials & Methods: A total of 100 children with clinical symptoms of that of pneumonia were enrolled. Complete demographic and clinical details of all the patients were obtained. According to ARI control program, pneumonia was classified into pneumonia, severe pneumonia and very severe pneumonia respectively. Lung ultrasound was done, and characterization of the features was done to find correlation with severity of pneumonia. Each hemithorax was divided into three parts: anterior, lateral, and posterior. The anterior part extended from the parasternal to the anterior axillary line; the lateral part was defined as the area between the anterior and the posterior axillary line; and the area from the posterior axillary line to the paravertebral line was defined as the posterior part. Each part can be subdivided into upper and lower halves. The probe was placed perpendicular, oblique, and parallel to the rib in the anterior, lateral, and posterior thorax and every intercostal space was examined in detail. All the results were recorded and evaluated using SPSS software. Results: A total of 100 children were evaluated. The mean age of the children was 12.9 years. Majority proportion of children were boys. Cough, fever, tachypnea, chest indrawing, lethargy and tachycardia were seen in 100 percent, 100 percent, 97 percent, 77 percent, 39 percent and 43 percent of the children respectively. Based on ARI criteria, 12 percent, 65 percent and 23 percent of the cases were of pneumonia, severe pneumonia and very severe pneumonia respectively. Out of 12 cases of pneumonia, an abnormal ultrasound was seen in 8.33 percent of the cases. Among 65 cases of severe pneumonia and 23 cases of very severe pneumonia, 26.15 percent, and 39.13 percent of the cases showed abnormal ultrasound. Conclusion: Lung ultrasound had very limited utility among childhood pneumonia cases.